Daya Terima Produk Inovasi Kombinasi Daun Kelor, Kolagen dan Daun Stevia sebagai Minuman Fungsional untuk Kesehatan - Diah Astika Winahyu; Shinta Wulandari; Leny Marlina; Zherly Anticha Pertiwi (Universitas Malahayati Lampung, 2025)
ABSTRACT The availability of Moringa leaves is quite abundant and easy to get. However, its use in food or beverage products is still relatively small, as it is only processed into meals. Processing Moringa leaves into a powder product as a functional drink, which is expected to last a long time and be ready for consumption. This type of research is non-experimental research with a descriptive approach using hedonic tests (liking tests). The hedonic test involved 30 panelists. The functional drink is made in three different formulations. In the appearance assessment, 33.34% of panelists chose the criteria that they really liked formulation III. As much as 30% of the panelists selected the aroma assessment as the criteria for really liking formulation I. The taste and texture of this functional drink were most liked in formulation III, with 40% and 33.3% respectively. In terms of appearance, taste and texture, the panelists chose the criteria that they really liked formulation III. Formulation I was selected by the panelists based on aroma criteria. Keywords: Functional Drinks, Moringa Leaves, Hedonic Test ABSTRAK Ketersediaannya daun kelor cukup melimpah dan mudah di dapatkan. Namun pemanfaatannya dalam produk pangan atau minuman masih tergolong sedikit seperti hanya diolah menjadi sayur. Mengolah daun kelor menjadi produk serbuk sebagai minuman fungsional, yang diharapkan dapat tahan lama dan siap untuk dikonsumsi. Jenis penelitian ini adalah penelitian non-eksperimental dengan pendekatan deskriptif dengan menggunakan uji hedonik (uji kesukaan). Dalam pengujian uji hedonik melibatkan 30 panelis. Minuman fungsional dibuat dalam tiga formulasi berbeda. Pada penilaian kenampakan 33,34% panelis memilih kriteria sangat suka pada formulasi III. Penilaian aroma sebanyak 30% panelis memilih kriteria sangat suka pada formulasi I. Rasa dan tekstur minuman fungsional ini paling banyak disukai pada formulasi III sebanyak 40% dan 33,3%. Dari segi kenampakan, rasa dan tesktur para panelis memilih kriteria sangat suka pada formulasi III. Formulasi I dipilih para panelis pada kriteria aroma. Kata Kunci: Minuman Fungsional, Daun Kelor, Uji Hedonik